Pengaruh suhu dan frekuensi penggunaan minyak goreng kelapa (Cocos nucifera L.) terhadap karakteristik fisikokimia kentang goreng - Sandra Sandra; Mustofa Lutfi; Nurul Istiqomah Choirunnisa (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
Frying oil is commonly used to fry food, especially in deep-fat frying methods at atmospheric pressure. Variations in fried food results are caused by various factors, including the type of food, type of frying oil, frying duration, frying oil temperature, and frying frequency. This study aims to investigate the effect of variations in temperature and frying frequency on the quality of French fries fried using self-produced coconut oil. Coconut oil was made from coconut milk that was pretreated by storing the coconut milk at a cold temperature before processing. Potatoes were fried at temperatures of 140 °C, 160 °C, 180 °C, and 200 °C, with the frequency process repeated 9 times with consecutive frying. Observations of water content, texture, and color of the French fries were evaluated at the end of the 3rd, 5th, 7th, and 9th frying for each frying temperature. The results showed that the temperature treatment at each frying frequency had no significant effect and the higher the temperature, the lower the water content. The higher the temperature, the higher the texture value (0.3467 kgf - 0.8067 kgf), and the greatest color change occurred at a temperature of 200 °C. Based on the research results, it is recommended to fry potatoes at a maximum temperature of 180 °C and with a frying frequency of no more than 9 times to obtain a good quality, crispy, and safe-to-eat French fries product.